Heterogeneous Copper-catalyst Anchored on Chitosan Schiff Basemodified Carbon Nanotubes for Click Reaction - Kwak, Soo-Jung; Kim, Seung-Hoi; Shin, Ueon Sang (Letters in Organic Chemistry, 2023)
A newly designed heterogeneous copper catalytic platform immobilizing copper (II) salt on chitosan Schiff base-modified carbon nanotubes was developed (Cu@CS-Py@CNT). The structure of the catalyst platform was fully characterized by spectroscopic analyses. The catalytic activity of the Cu@CS-Py@CNT was investigated in a one-pot synthesis of 1,4-disubstituted 1,2,3-triazoles by the regioselective click reaction using various benzyl halides or their surrogates, terminal alkynes, and sodium azide in an aqueous environment without using any external Cu-reducing agents.
Keywords: heterogeneous copper